Comparative effects of a candidate modified-risk tobacco product Aerosol and cigarette smoke on human organotypic small airway cultures: a systems toxicology approach. Issue 6 (5th October 2017) - Iskandar, Anita R.; Martinez, Yannick; Martin, Florian; Schlage, Walter K.; Leroy, Patrice; Sewer, Alain; Torres, Laura Ortega; Majeed, Shoaib; Merg, Celine; Trivedi, Keyur; Guedj, Emmanuel; Frentzel, Stefan; et al.
Graphical Abstract: Abstract: Using an in vitro human small airway epithelium model, we assessed the biological impact of an aerosol from a candidate modified-risk tobacco product, the tobacco heating system (THS) 2.2, to investigate the potential reduced risk of THS2.2 aerosol exposure compared with cigarette smoke. Following the recommendations of the Institute of Medicine and the Tobacco Product Assessment Consortium, in which modified-risk tobacco products assessment should be performed in comparison with standard conventional products, the effects of the THS2.2 aerosol exposure on the small airway cultures were compared with those of 3R4F cigarette smoke. We used a systems toxicology approach whereby elucidation of toxic effects is derived not only from functional assay readouts but also from omics technologies. Cytotoxicity, ciliary beating function, secretion of pro-inflammatory mediators and histological assessment represented functional assays. The omics data included transcriptomic and miRNA profiles. Exposure-induced perturbations of causal biological networks were computed from the transcriptomic data. The results showed that THS2.2 aerosol exposure at the tested doses elicited lower cytotoxicity levels and lower changes in the secreted pro-inflammatory mediators than 3R4F smoke. Although THS2.2 exposure elicited alterations in the gene expression, a higher transcriptome-induced biological impact was observed following 3R4F smoke: The effects of THS2.2 aerosol exposure, if observed, were mostly transient and diminished more rapidly after exposure than those of 3R4F smoke. The study demonstrated that the systems toxicology approach can reveal changes at the cellular level that would be otherwise not detected from functional assays, thus increasing the sensitivity to detect potential toxicity of a treatment/exposure.